Quantitative phytochemical screening and acute oral toxicity study of Piper betle and Persicaria odorata leaf extract in broiler chickens - Basit, Muhammad Abdul; Abdul Kadir, Arifah; Kaka, Ubedullah; Javid, Muhammad Arshad; Saleem, Muhammad Usman; Ahmed Bhatti, Sheraz; Farooq, Abdul Asim; Murtaza, Saeed; Waqas, Muhammad Yasir; Nawaz, Muhammad; Muhammad Arshad, Hafiz (Green Publication, 2024)
Medicinal plants like herbs are used extensively as an alternative poultry feed additive, replacing antimicrobial drugs. However, these herbs and their bioactive compounds may contain toxic substances that may be harmful. Thus, the present study was conducted to estimate the secondary phytochemical metabolites and acute toxicity of methanolic leaf extract of Piper betle (Pb) and Persicaria odorata (Po) in broiler chickens. A total of 35 broiler chicks were used in this study. The birds were divided into 7 groups randomly on the 21st day of their age. A single oral dose of methanolic leaf extract of P. betle and P. odorata at the rate of 500mg/kg, 1000 mg/kg, and 2,000 mg/kg body weight, was orally gavaged in treated chickens. At the same time, the control group received 0.5% carboxymethyl cellulose (CMC) as a placebo. Quantitative phytochemical screening showed positive quantification of eugenol and quercetin from Pb and Po methanolic leaf extract.